PEREMPUAN DALAM PERIKANAN DAN AKUAKULTUR DI KABUPATEN INDRAGIRI HILIR RIAU - Rujiah Rujiah; KMS Novyar Satriawan Fikri; Marlina Marlina; Mulono Apriyanto (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2021)
In terms of participation excellence, the fisheries sector of Indragiri Hilir Regency is gender biased. Pia dominates the scene, will hold leading positions such as ownership, control, and access to the productive resources of aquaculture production systems, as well as ownership of fishing vessels and equipment in the fishing sector. These roles give them the benefit of financial by providing investment opportunities, loan facilities, and import and export licenses, among others. Despite the economic potential of small-scale fisheries and aquaculture, women invest very little in the aquaculture, artisanal and industrial sectors. Women take a secondary role in processing and marketing, delaying major decisions for male counterparts. The underlying socio-cultural norms and gender relationships emphasized by intersectionality are often barriers to owning, accessing, or controlling productive resources and other inputs. Gender mainstreaming appears to be a very recent development in the fisheries sector. The goal of the study is the reorientation of women, especially those working in small-scale fisheries, including fisheries and aquaculture, toward active and significant participation in boat owner contribution, productivity, and policy/decision-making. Secondary data and conclusions from previous studies, especially reports and reviews from other districts,compared to what is available in Indragiri Hilir Regency. As a result, we propose expanding social entrepreneurship initiatives, bootstrapping,and social capital, among other interventions, to increase women's participation in the fisheries sector. Dalam hal keunggulan partisipasi, sektor perikanan Kabupaten Indragiri Hilir bias gender. Pia mendominasi tempat kejadian, akan memegang posisi terkemuka seperti kepemilikan, kontrol, dan akses ke sumber daya produktif sistem produksi akuakultur, serta kepemilikan kapal penangkap ikan dan peralatan di sektor perikanan. Peran-peran ini menguntungkan mereka secara finansial dengan memberikan peluang investasi, fasilitas pinjaman, dan lisensi impor dan ekspor, antara lain. Terlepas dari potensi ekonomi perikanan dan akuakultur skala kecil, perempuan berinvestasi sangat sedikit di sektor akuakultur, artisanal dan industri. Perempuan mengambil peran sekunder dalam pengolahan dan pemasaran, menunda keputusan besar untuk rekan-rekan laki-laki. Norma-norma sosial-budaya yang mendasari dan hubungan gender yang ditekankan oleh interseksionalitas sering menjadi hambatan untuk memiliki, mengakses, atau mengendalikan sumber daya produktif dan input lainnya. Pengarus utamaan gender tampaknya menjadi perkembangan yang sangat baru di sektor perikanan. Tujuan dari penelitian adalah reorientasi perempuan, terutama mereka yang bekerja di perikanan skala kecil, termasuk perikanan dan akuakultur, menuju partisipasi aktif dan signifikan dalam kontribusi pemilik kapal, produktivitas, dan kebijakan / pengambilan keputusan. Data sekunder dan kesimpulan dari penelitian sebelumnya, terutama laporan dan ulasan dari Kabupaten lain, dibandingkan dengan apa yang tersedia di Kabupaten Indragiri Hilir. Sebagai hasilnya, kami mengusulkan perluasan inisiatif kewirausahaan sosial, kapal penangkap ikan (bootstrapping), dan modal sosial, di antara intervensi lainnya, untuk meningkatkan partisipasi perempuan di sektor perikanan.